EPIFIT DAN LIANA PADA POHON DI HUTAN PAMAH PRIMER DAN BEKAS TERBAKAR KALIMANTAN TIMUR, INDONESIA - Herwint SIMBOLON (BERITA BIOLOGI, 2007)
Epiphytes and lianas on the trees grown in three categories of gradation of Mixed Dipteroearp Forests (natural, lightly degraded and heavily degraded after forest fires) have been studied in Bukit Bangkirai Nature Recreation Park, East Kalimantan.166 species of epiphytes and lianas were found in those three study plots, among them 89; 134 and 56 species were distributed in the natural, lightly degraded and heavily degraded forest plots, respectively. 30 species were distributed widely in three types of forests, 37 species were tend to be the shade tolerant species and 16 species as light demanding species, since they were distributed in the closed and open forests, respectively. The most common species that distributed in those three studied plots were Derris elegans, Spatholobus gyrocarpus and Embelia ribes. Number of epiphytes and lianas on the single individual tree host were increase as the tree diameter increased. Number of species of epiphytes and lianas on a species of host were increased as the number of individuals were increased, indicates that most of these epiphytes and lianas were not host specific.